Odpowiedź :
Odpowiedź:
zad4
A)[tex]\frac{2\sqrt{6} -\sqrt{16} }{2} =\frac{2\sqrt{6} -4}{2} =\sqrt{6} -2[/tex]
B.[tex]\frac{3-\sqrt{3} }{\sqrt{3} } *\frac{\sqrt{3} }{\sqrt{3} } =\frac{3\sqrt{3}-3}{3} =\sqrt{3} -1[/tex]
C.[tex]\frac{\sqrt{25} +\sqrt{5} }{\sqrt{5} } =\frac{5+\sqrt{5} }{\sqrt{5} }*\frac{\sqrt{5} }{\sqrt{5} } =\frac{5\sqrt{5}+5 }{5} =\sqrt{5} +1[/tex]
D.[tex]\frac{\sqrt{2}*\sqrt{3} }{\sqrt{54} } =\frac{\sqrt{6} }{\sqrt{54} } =\sqrt{\frac{6}{54} } =\sqrt{\frac{1}{9} } =\frac{1}{3}[/tex] to jest liczba wymierna
odp.D
zad5
[tex]\frac{\sqrt[3]{-16}*\sqrt[3]{-16} }{\sqrt[3]{-4} } =\sqrt[3]{-16} *\sqrt[3]{4} =\sqrt[3]{-16*4}=\sqrt[3]{-64} =-4[/tex]
odp.C
zad 6
[tex]\frac{5^5*3+2*5^5}{5^6:5^2} =\frac{5^5(3+2)}{5^4} =\frac{5^5*5}{5^4} =5^{6-4}}=5^2=25[/tex]
odp.C
Szczegółowe wyjaśnienie: